Review on the Vascularization of Organoids and Organoids-on-a-Chip - Zhao, Xingli; Xu, Zilu; Xiao, Lang; Shi, Tuo; Xiao, Haoran; Wang, Yeqin; Li, Yanzhao; Xue, Fangchao; Zeng, Wen (Frontiers in Bioengineering and Biotechnology, 2021)
The use of human cells for the construction of 3D organ models in vitro based on cell self-assembly and engineering design has recently increased in popularity in the field of biological science. Although the organoids are able to simulate the structures and functions of organs in vitro, the 3D models have difficulty in forming a complex vascular network that can recreate the interaction between tissue and vascular system. Therefore, organoids are unable to survive, due to the lack of oxygen and nutrients, as well as the accumulation of metabolic waste. Organoids-on-a-chip provide a more controllable and favorable design platform for co-culture of different cells and tissue types in organoid systems, overcoming some of the limitations present in organoid culture. However, the majority of them has vascular networks that are not adequately elaborate to simulate signal communications between bionic microenvironment (e.g. fluid shear force) and multiple organs. Here, we will review the technological progress of the vascularization in organoids and organoids-on-a-chip and the development of intravital 3D and 4D bioprinting as a new way for vascularization, which can aid in further study on tissue and organ development, disease research and regenerative medicine.